Estudio de factibilidad para el uso de refrigerantes R134a, R123, R600a en una bomba de calor asistida por energía solar utilizando un compresor de 1/6 hp - Valenzuela Pazmiño, Max Henry (2018)
A direct-expansion solar-assisted heat pump system by using R600a as refrigerant is described in this project. The system mainly includes a flat-plate solar collector of total are 1 m2, acting as an evaporator, a hermetically sealed reciprocating type compressor of 1/6 hp, a straight copper tube having an inner diameter of 3/16” as condenser and an electronic expansion valve. Data was observed every five minutes, during four tests per day, tests have an average period of 70 minutes. The system objective was to raise the water temperature to about 45 ° C. The highest temperature observed inside the water storage tank was 45.3 ° C in a period of 75 minutes. The system was influenced by varying weather conditions. An average radiation and an average room temperature of 556.75 W/m2, 20.7 ° C respectively was present those days. This type of system has a high initial investment, however, it can be recovered in the long term and they are friendly to the environment by not using fossil fuels, in addition to the possible eradication of hundreds of kilograms of CO2 per year.